2014
DOI: 10.1017/s1743921314013519
|View full text |Cite
|
Sign up to set email alerts
|

Shape estimation for Košice, Almahata Sitta and Bassikounou meteoroids

Abstract: This paper is concerned with a meteoroid shape estimation technique based on statistical laws of distribution for fragment masses. The idea is derived from the experiments that show that brittle fracturing produces multiple fragments of size lesser than or equal to the least dimension of the body. The number of fragments depends on fragment masses as a power law with exponential cutoff. The scaling exponent essentially indicates the initial form of the fragmented body. We apply the technique of scaling analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…The southern part of the strewn field was sampled furthest perpendicular to the Farnocchia et al (2017) trajectory, and from those meteorites alone the large masses are spread with FWHM = 3.7 km. Vinnikov et al (2015) found different mass size distributions in each regime.…”
Section: Introductionmentioning
confidence: 92%
“…The southern part of the strewn field was sampled furthest perpendicular to the Farnocchia et al (2017) trajectory, and from those meteorites alone the large masses are spread with FWHM = 3.7 km. Vinnikov et al (2015) found different mass size distributions in each regime.…”
Section: Introductionmentioning
confidence: 92%
“…e loading pressure in front of the body produces the rock fracture when it overcomes its tensile strength. As a natural consequence, meteorite falls often deliver tens to hundreds of stones, just after this type of break-ups [69,70]. We have previously described such behavior when discussing the evolution of Chelyabinsk.…”
Section: Implications For Impact Hazardmentioning
confidence: 98%
“…e same approach, applying the power law distribution with an exponential cutoff, was used in [61][62][63][64] to estimate the shape of original object when considering Košice, Bassikounou, Almahata Sitta, and Sutter's Mill meteorite falls. A curve of the cumulative mass distribution of collected fragments from the Mbale meteorite shower was constructed in [65], and it was shown that a simple power law distribution (straight line in log-log coordinates) fitted the part of this curve for large fragments but could not describe the whole curve.…”
Section: Introductionmentioning
confidence: 99%